If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -9)(x + -5) = 45 Reorder the terms: (-9 + x)(x + -5) = 45 Reorder the terms: (-9 + x)(-5 + x) = 45 Multiply (-9 + x) * (-5 + x) (-9(-5 + x) + x(-5 + x)) = 45 ((-5 * -9 + x * -9) + x(-5 + x)) = 45 ((45 + -9x) + x(-5 + x)) = 45 (45 + -9x + (-5 * x + x * x)) = 45 (45 + -9x + (-5x + x2)) = 45 Combine like terms: -9x + -5x = -14x (45 + -14x + x2) = 45 Add '-45' to each side of the equation. 45 + -14x + -45 + x2 = 45 + -45 Reorder the terms: 45 + -45 + -14x + x2 = 45 + -45 Combine like terms: 45 + -45 = 0 0 + -14x + x2 = 45 + -45 -14x + x2 = 45 + -45 Combine like terms: 45 + -45 = 0 -14x + x2 = 0 Solving -14x + x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-14 + x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-14 + x)' equal to zero and attempt to solve: Simplifying -14 + x = 0 Solving -14 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + x = 0 + 14 x = 0 + 14 Combine like terms: 0 + 14 = 14 x = 14 Simplifying x = 14Solution
x = {0, 14}
| 13x=2x-66 | | -7+7x=21 | | 5x^3+40x^2+75x=0 | | 4(n-3)=16 | | 6t+2s=8 | | 3r^3+12r^2-36r=0 | | -1.33x=-1.33x-5.66 | | 5/2=4g/5 | | 30x^2+31xy+5y^2=0 | | (2w-3)w-27=0 | | 2.8x+4.5=.3-.5x | | 0.83+3j=0.6 | | 9v^2-13v+3=0 | | 36p^3q-25pq^3=0 | | 7x+14-6x-16=18 | | (2w+1)w-66=0 | | .75=.375x-1.50 | | 2(g+3)+5(1-g)=10 | | 5a^2+33a+18=0 | | -3-7x=-87 | | 2s+6t=8 | | 8x+3-2x=3x+12 | | 4+6x=40 | | 4y+13=2y+7 | | 5(3)-2y=-13 | | 7x^2=182 | | x/3=-4-(-3) | | 8-7x=78 | | -9+7x=-9 | | L(2w+5)=65 | | ((2x^2)4)-16=0 | | 3x-5x=14 |